Two showy traits, scent emission and pigmentation, are finely coregulated by the MYB transcription factor PH4 in petunia flowers. Issue 3 (25th June 2015) - Cna'ani, Alon; Spitzer‐Rimon, Ben; Ravid, Jasmin; Farhi, Moran; Masci, Tania; Aravena‐Calvo, Javiera; Ovadis, Marianna; Vainstein, Alexander
Summary: The mechanism underlying the emission of phenylpropanoid volatiles is poorly understood. Here, we reveal the involvement of PH4, a petunia MYB‐R2R3 transcription factor previously studied for its role in vacuolar acidification, in floral volatile emission. We used the virus‐induced gene silencing (VIGS) approach to knock down PH4 expression in petunia, measured volatile emission and internal pool sizes by GC‐MS, and analyzed transcript abundances of scent‐related phenylpropanoid genes in flowers. Silencing of PH4 resulted in a marked decrease in floral phenylpropanoid volatile emission, with a concurrent increase in internal pool levels. Expression of scent‐related phenylpropanoid genes was not affected. To identify putative scent‐related targets of PH4, we silenced PH5, a tonoplast‐localized H + ‐ATPase that maintains vacuolar pH homeostasis. Suppression of PH5 did not yield the reduced‐emission phenotype, suggesting that PH4 does not operate in the context of floral scent through regulation of vacuolar pH. We conclude that PH4 is a key floral regulator that integrates volatile production and emission processes and interconnects two essential floral traits – color and scent.